2003
DOI: 10.1007/bf02970135
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of yellow sand in lung epithelial cells

Abstract: The present study was carried out to observe the cytotoxicity of yellow sand in comparison with silica and titanium dioxide in a rat alveolar type II cell line (RLE-6TN). Yellow sand (China Loess) was obtained from the loess layer in the Gunsu Province of China. The mean particle diameter of yellow sand was about 0.003 +/- 0.001 mm. Major elements of yellow sand were Si(27.7 +/- 0.6%), Al(6.01 +/- 0.17%), and Ca(5.83 +/- 0.23%) in that order. Silica and yellow sand significantly decreased cell viability and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…To this end, we incubated H441 cells with 0,10, and 100 μg/mL of nano-TiO 2 for 1 h, and assessed the concentration of H 2 O 2 in their supernatants. Consistent with previous findings (Kim et al, 2003), significantly increased levels of H 2 O 2 levels were detected in H441 cells exposed to 100 μg/mL of nano-TiO 2 for 1 h as compared to controls (4.78 ± 0.09 μM vs. 1.47 ± 0.06 μM, p<0.01; 3-fold increase as shown in Figure 2b). Exposure of H441 cells to 10 μg/mL of TiO 2 did not increase H 2 O 2 concentrations in the extracellular medium (1.59 ± 0.08 μM vs. 1.47 ± 0.06 μM).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To this end, we incubated H441 cells with 0,10, and 100 μg/mL of nano-TiO 2 for 1 h, and assessed the concentration of H 2 O 2 in their supernatants. Consistent with previous findings (Kim et al, 2003), significantly increased levels of H 2 O 2 levels were detected in H441 cells exposed to 100 μg/mL of nano-TiO 2 for 1 h as compared to controls (4.78 ± 0.09 μM vs. 1.47 ± 0.06 μM, p<0.01; 3-fold increase as shown in Figure 2b). Exposure of H441 cells to 10 μg/mL of TiO 2 did not increase H 2 O 2 concentrations in the extracellular medium (1.59 ± 0.08 μM vs. 1.47 ± 0.06 μM).…”
Section: Resultssupporting
confidence: 92%
“…Moreover, H 2 O 2 has been shown to be produced in the cell supernatant of a rat alveolar type II cell line after incubation with nano-TiO 2 for 18h (Kim et al, 2003). H 2 O 2 is a non-radical ROS that is also produced in low concentrations by cells for signaling purposes (Casanova et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Geng et al (2005) used human equivalent doses reflective of a typical blowing sand day in vitro and found that ASD induced oxidative stress on alveolar macrophages, increased plasma membrane fragility, and elevated intracellular calcium levels, leading to cytotoxicity and cell death. Kim et al (2003) showed that ASD were specifically cytotoxic to rat alveolar type II cells and that reactive oxygen and nitrogen species may be involved. Contaminants including endotoxin and β-glucan absorbed onto the ASD surface, increasing the expression of proinflammatory molecules and subsequent neutrophilic inflammation (Yanagisawa et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…In Korea, yellow dust storms are usually observed in March and May every year, when the level of PM 10 exceeds the level of environmental standard by two or three times (28). The size of particulate matter from the yellow dust is mainly 3 µm (29). This range of particulate matter is easily respirable.…”
Section: Discussionmentioning
confidence: 99%